ANALISIS SEMIOTIK PIDATO GANJAR PRANOWO PADA PENETAPAN NOMOR URUT CALON PRESIDEN DI KPU - Fida Ul Haq, Muhammad; Anoegrajekti, Novi (JURNAL SKRIPTA, 2024)
The 2024 Presidential Election is less than three months away. The Election Commission (KPU) has officially announced the presidential and vice-presidential candidates who will be running in the election. This research aims to uncover the meaning of Ganjar Pranowo's speech, after the announcement of the ballot number by the KPU. The research methodology employs the semiotics analysis of Ferdinand De Saussure, focusing on signifiers and signifieds. The approach used in this study is a qualitative descriptive approach. Data collection methods include documentation and literature review. The findings of this research reveal Ganjar Pranowo's explanation of the political phenomena leading up to the Presidential Election. He also calls on all Indonesian citizens to oversee the election process to prevent any irregularities.